PENINGKATAN HASIL BELAJAR DALAM MATA PELAJARAN PKN MELALUI MODEL PEMBELAJARAN KOOPERATIF TIPE STUDENT FACILITATOR AND EXPLAINING DI KELAS IV SDN 08 KUMBAYAU - MASFITRYAN MASFITRYAN (JURNAL MANAJEMEN PENDIDIKAN, 2019)
Based on Student Learning Outcomes of Class IV SDN 08 Kumbayau in PKN subjects it was found that Student Learning Outcomes in PKN subjects were still very low. The purpose of this study was to describe and obtain information about Improving Student Learning Outcomes in PKN subjects through the cooperative learning model type Student Facilitator and Explaining in Class IV SDN 08 Kumbayau. This research is a class action research. Research procedures in this study include planning, action, observation and reflection. This research consisted of two cycles with four meetings. The research subjects consisted of 18 students of Class IV SDN 08 Kumbayau. Research data were collected using Observation sheets. Data were analyzed using percentages.Based on the results of research and discussion that have been presented in the previous chapter, it can be concluded that it can be concluded that the model of demonstration learning can improve student learning outcomes in PKN subjects in Class IV SDN 08 Kumbayau. Student Learning Outcomes from cycle I to cycle II. Student learning outcomes in the first cycle was 68.89 (enough) increased to 77.78 (good) with an increase of 8.89 (good).